Benign solvents for recycling and re-use of a multi-layer battery pouch. Issue 12 (24th May 2022) - Marshall, Jean E.; Middleton, Bethany; Gastol, Dominika; Sommerville, Roberto; McElroy, Con R.; Kendrick, Emma; Goodship, Vannessa
Abstract : This article describes a process for the repair and re-use of an aluminium-containing pouch used as an outer casing for a Lithium-ion battery cell. Abstract : This article describes a process for the repair and re-use of an aluminium-containing pouch used as an outer casing for a Lithium-ion battery cell. As Lithium-ion batteries become more widespread, particularly with their increasing use in the automotive industry and in consumer electronics, recycling them is becoming an important challenge. Current recycling approaches for Li-ion batteries focus on reclamation of the high-value metals found in the electrodes. However, in order to minimise the environmental impact of the battery it would be optimal to be able to reclaim and re-use other components. Since many battery cells consist of an electrode stack held inside an outer pouch, we herein describe the structure of such a pouch and suggest methods for selectively stripping and repairing the inner layer, allowing the material to be re-used. We investigated the use of three different solvents (xylene, limonene, and 2, 2, 5, 5-tetramethyloxolane) for the selective stripping of the polypropylene (PP) layer on the inner side of a pouch material. Each solvent was tested on both 'pristine' pouch material (as obtained from the manufacturer) and pouch material that had previously been part of a battery. For 'used' pouch material, the overall thickness of the film decreased from 150–160 μm to 70–80 μm in under 1 h for all three solvents (corresponding to the removal of the PP layer), whereas for the 'pristine' pouch higher temperatures and longer times were required; this result is suggestive of some polymer degradation during the life of the pouch. Following the removal of the PP layer, virgin PP was subsequently added to renew the multi-layer structure.